Impact of stirring time and the corresponding growth mechanism in the solvothermal synthesis of WO3 nanostructures. Issue 4 (2nd October 2022) - Jin, Changhyun; Lim, Jong-Chan; Kim, Min Young; Choi, Myung Sik; Kim, Sang-Il; Baek, Seung-Hyub; Kim, Sun-Jae; Lee, Seung Yong; Kim, Hyun-Sik; Lee, Kyu Hyoung
ABSTRACT: WO3 nanostructures with different morphologies and dimensions were fabricated via solvothermal synthesis by adjusting the stirring time of the precursor solution. Ethanol-based solutions of the WCl6 precursor with various colors (dark green, yellow, white, blue, and blue-black) were prepared, and this triggered a significant change in the growth behavior during the evolution of WO3 nanostructures. Controlling the initial state of the precursors in solution enabled sequential nucleation and growth which resulted in the production of zero-to-three-dimensional nanostructures including nanoparticles, a mixture of nanosheets and nanoparticles, jointed-nanosheets, and three-dimensionally clustered jointed-nanosheets. The crystallographic characteristics (preferred orientation along the (002) plane) and the concentration of surface oxygen vacancies were also controllable, suggesting the formation of nanostructures with tuneable surface reactivity. Differing NO2 sensing performances were observed because of the variation in configurations of the WO3 nanostructures.